The Brexit revolution: New political conditions change the dynamics of the next phase of EU-UK negotiations - Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2020)
Following the United Kingdom's withdrawal from the European Union (EU), the Brexit negotiations are entering the decisive next phase: In a transition period of now only 10 months, the future relationship between the EU and the United Kingdom with regard to economic, internal security, and foreign policy as well as an overall institutional framework must be negotiated. But the signs point to confrontation. The main aim of the domestically strengthened British government is absolute dissociation from the EU; the list with potential points of conflict with the Union's negotiation objectives is long. Together, the negotiators must find a new model of cooperation between partnership and competition.
Keywords: 320